Conhecimentos, concepções e práticas de professores de educação especial : o modelo médico-psicológico ainda vigora? - Camizão, Amanda Costa (2016)
In this research we aim to analyze knowledge, concepts and special education teacher’s practices in specialized education service at early childhood institutions for children with intellectual disabilities, considering the medical model. We contemplate the historical-cultural perspective and historical-critical pedagogy as the theoretical basis of the study and Vygotsky (2007, 2012), Leontiev (2005), Saviani (2008, 2013, 2014) are the main interlocutors. These authors provide us a contribution regarding the medicalization of education. This research has a qualitative nature of a case study. For production of the data, we applied semi-structured interviews, document analysis and field diary record. The field research was conducted in seven municipal centers of early childhood education inside the Metropolitan Region. As subjects of the study, we have ten special education teachers who work for children with intellectual disabilities. The data produced through the interviews indicates that teachers have shown a gap of theoretical studies by the time they graduated, focusing on pathological knowledge of children. Regarding his views, teachers tended to associate the disability of the child to a limitation associated to reports of specialized educational services, the report is seen as a starting point for research and organization of care. The analysis of practices was mainly marked by the influence of the knowledge and conceptions of teachers in teaching activities. The data also show that the city has invested heavily in training for special education teachers, however, it has focused on the coming of health professionals to perform these formations, which, in turn, directly influences the knowledge, concepts and practices of these teachers. The survey showed that, it is still present medical model in special education teacher performance for children from birth to five years, this influence is historic and strengthens when knowledge arising from health excels the educational knowledge.